2013
DOI: 10.3892/or.2013.2662
|View full text |Cite
|
Sign up to set email alerts
|

Slit2 expression and its correlation with subcellular localization of β-catenin in gastric cancer

Abstract: Gastric cancer is the fourth most common cancer worldwide. Several signaling pathways are involved in gastric cancer development and progression. Slit2 was recently found to be involved in cancer; however, its expression pattern in gastric cancer has not been discovered yet. In the present study, we investigated the expression of Slit2 in human gastric cancer and its correlation with the expression and subcellular localization of β-catenin. Immunohistochemistry (IHC) staining revealed that Slit2 was highly exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 20 publications
2
15
0
Order By: Relevance
“…5-7 The Slit-Robo signalling pathway plays important roles not only in neuronal guidance but also during cell migration of a wide range of cell types. 17,18 In contrast, two other reports suggested that Robo1 might promote tumorigenesis. 16 However, the precise function of the Slit-Robo pathway in the development of GC remains ill-defined.…”
Section: Introductionmentioning
confidence: 89%
“…5-7 The Slit-Robo signalling pathway plays important roles not only in neuronal guidance but also during cell migration of a wide range of cell types. 17,18 In contrast, two other reports suggested that Robo1 might promote tumorigenesis. 16 However, the precise function of the Slit-Robo pathway in the development of GC remains ill-defined.…”
Section: Introductionmentioning
confidence: 89%
“…Knockdown of Slit2 activates β-catenin signaling through AKT. Our previous study revealed a correlation between loss of Slit2 expression and nuclear β-catenin in gastric cancer tissues (23). AKT, on the other hand, is one of the major kinases that phosphorylated and inactivated GSK3β and subsequently released and activated β-catenin signaling.…”
Section: Knockdown Of Slit2 Activates Akt-mediated Survival Signalingmentioning
confidence: 97%
“…Thus, the role of Slit2 in cancer is distinct depending on the cancer type. Our previous studies (15,16) in gastric cancer indicated that Slit2 is a tumor suppressor. The expression of Slit2 was higher in gastric patients with less advanced clinicopathological features.…”
Section: Discussionmentioning
confidence: 98%
“…Our previous study identified Slit2 as a diagnosis and prognosis marker in gastric cancer. Mechanistically, it participates in gastric cancer oncogenesis and metastasis through regulating the AKT/β-catenin pathway (15,16).To the best of our knowledge, the expression pattern of Slit2 and its correlation with clinicpathological parameters of PTC has not been previously reported. In the present study, we examined Slit2 expression in transcriptional and protein level, and then analyzed the correlation between Slit2 expression and the clinicopatholocical characteristics of PTC.…”
mentioning
confidence: 90%
See 1 more Smart Citation